Balancing the challenges of high-stakes testing, accountability and students’ well-being - Hopfenbeck, T (Taylor and Francis, 2017)
In the lead article in this regular issue, Stenlund, Eklöf, and Lyrén (2017) have investigated whether different groups of test-takers vary in their reported test-taking behaviour in a highstakes test situation. The study involves N = 1129 students (63.2% females, mean age 22) who sat for the Swedish scholastic aptitude test (SweSAT) – a paper and pencil test with multiple-choice items used for selection to higher education in Sweden. SweSAT measures what is seen as general abilities and knowledge. Sweden has a centralised admission system with the regulations that in cases where there are more applicants than places to higher education, the candidate should be admitted based upon their SweSAT scores and upper secondary school GPA. In other words, the stakes are high when students sit for the SweSAT. Since the test was introduced in 2011, between 40,000 and 80,000 test-takers sit for the test twice a year. The authors report that as many as 25% are repeaters, but in their study, they have focused only on students who sat the test for the first time. The participating students responded to an online questionnaire, reporting on their test-taking strategies such as structural organisation, time management and testwiseness strategies. The authors also included items on test anxiety and test motivation.